Granulomatosis Wegener dengan Antineutrophil Cytoplasmic Antibodies (ANCA) Negatif pada Laki-laki Usia 38 Tahun - Achmad Satya Negara; Harijono Kariosentono; Endra Yustin Elistasari (PT Dexa Medica, 2021)
Background : Wegener’s granulomatosis or granulomatosis with polyangiitis is a systemic necrotizing vasculitis, which affects small- and medium-sized blood vessels. This disease is often associated with antineutrophil cytoplasmic antibodies (ANCA). Etiology of Wegener’s granulomatosis may originate from infectious, environmental, chemical, toxic or pharmacological triggers in people who are genetically predisposed to this autoimmune disease. The disease can present with nonspecific symptoms such as malaise, myalgia, arthralgia, anorexia, and weight loss. Skin manifestations of Wegener’s granulomatosis includes leukocytoclastic vasculitis, purpura, ulcer and subcutaneus nodul. It also known could affect different organs. Case: A 38-year-old man came with a chief complaint of erythematous patches and stiffness on his face, body, arms and legs. The dermatological status showed a saddle nose and discrete multiple purpura on the superior and inferior extremities. ANCA examination result was negative. Histopathological examination of the epidermal layer showed dense proliferation of lymphocyte cells, perivascular infiltrates and a few neutrophil cells. In the dermis layer, there were granulomas consisting of many epitheloid histiocytes and foamy macrophages also damaged blood vessels with neutrophil infiltration on the walls and erythrocyte extravasation. Discussion: Wegener’s granulomatosis is a rare autoimmune disease of localized granulomatous inflammation of the upper and lower respiratory tract and systemic vasculitis associated with ANCA. Symptoms that arise in Wegener’s granulomatosis are often mild at first, but may progress to a more severe clinical features. A negative ANCA examination cannot immediately rule out the diagnosis. Initial therapy for Wegener’s granulomatosis are cyclophosphamide and glucocorticoids for 3-6 months. Patient showed clinical improvement with the reduction of purpura throughout the body after five weeks treatment.